Sistem pengumpulan pengetahuan penyelesaian masalah ISO 9000 - Muhammad, Mohamad Syakiran (2004)
IS0 9001 is a quality system that is fast becoming popular and has also become a taken path of service based industries around the world including the service sector. However, the process of acquiring certification seems to be riddled with problems. A big number of organizations around the world use a number of techniques and technologies to manage knowledge thoroughly. Their objective is to help subordinates/workers improve their methods of giving to the organization in terms of co-operation, experience and knowledge sharing, and also learning from other co-workers. Literature reviews have been conducted to prove that knowledge management (KM) support applications towards respective communities of practise (COP) have indeed been IS0 certified. Key points of the developed system have been adapted &om Nonaka and Takeuchi KM model with support of the IS0 9000 problem solving methods. This will help the COP in terms of experience sharing from more advanced organizations. The Sistem Pengumpulan Pengetahuan Penyelesaian Masalah IS0 9000' is proposed to help create a knowledge sharing environment between organizations that intend on acquiring IS0 certification. The main objective is to acquire the experience knowledge of successfid IS0 certified organizations though co-operation, experience and knowledge sharing and also to learn from others experience.